Lenin and the revolutionary party - Blanc, Paul Le 1947- (Chicago, Illinois , Delhi : Haymarket Books; AAKAR, 2016)
"This study of Lenin's conception of the revolutionary party, and its place in Marxist thought, gives a vibrant sense of the historical context--both Russian and international--in which Lenin's views were shaped and upon which they had such a profound impact"--Provided by publisher.
Note to the Haymarket Books edition -- 1. Introduction: Authentic Leninism -- What Leninism is not -- A living organism and phases of development -- 2. The context of Lenin's early organizational perspectives -- Dimensions of Lenin's activity -- Lenin's programmatic orientation -- Ferment in the Russian working class -- 3. Revolutionary program, cohesive organization -- Organizational implications of revolutionary program -- Adapting to Russian conditions -- 4. The birth of Leninism -- What is to be done? -- The stormy beginning of Bolshevism -- 5. Questions and problems -- Luxemburg and Lenin -- Revolutionary committees distinct from the workers -- Was the Bolshevik/Menshevik split "unprincipled"? -- 6. The test of revolution -- The revolutionary program -- Revolution without Bolsheviks? -- The party broadens -- 7. The meaning of democratic centralism -- Democratic centralism in the RSDLP -- Democratic centralism in the bolshevik party -- Lenin's "iron grip" -- 8. Preparing for revolution -- Overcoming ultraleftism -- Philosophy and revolutionary program -- The Bolsheviks become a party -- 9. The almost-revolution -- Worker-Bolsheviks -- The upsurge -- 10. Party and war -- Revolutionary internationalism -- The actuality of world revolution -- How the party functioned -- 11. Party and revolution -- Overthrowing Tsarism but not taking power -- Reorientation -- Diversity and discipline -- Party and masses in the workers' revolution -- 12. After taking power -- State, revolution, and socialist democracy -- Crisis of Bolshevism -- Communist International -- A note on Lenin's authority -- Bureaucratization after Lenin -- The fate of the Comintern -- 13. Conclusion -- Reflections on the Leninist Party -- Problems of Leninism.
"Published 1993 by Humanity Books in New York"--Title page verso.
Bibliography : p. 353-368
Includes bibliographical references and index
Keywords: Lenin, Vladimir Ilʹich, -- 1870-1924 -- Political and social views; x; x; Socialism -- Russia -- History; Philosophy, Marxist -- History; Revolutions -- Philosophy -- History; Russia -- Politics and government -- 1894-1917.; Soviet Union -- Politics and government -- 1917-1936.